MicroRNA-301a-3p promotes pancreatic cancer progression via negative regulation of SMAD4 - Xia, Xiang (Oncotarget, 2015)
BACKGROUND: Aim to determine the clinicopathological and prognostic role of miR-301a-3p in pancreatic ductal adenocarcinoma(PDAC), to investigate the biological mechanism of miR-301a-3p in vitro and in vivo. METHODS: By tissue microarray analysis, we studied miR-301a-3p expression in PDAC patients and its clinicopathological correlations as well as prognostic significance. qRT-PCR was used to test miR-301a-3p expression in PDAC tissues and cell lines. Functional experiments including in vitro and in vivo were performed. RESULTS: Significantly higher expression of miR-301a-3p were found in PDAC patients with lymph node metastasis and advanced pathological stages and identified as an independent prognostic factor for worse survival. In PDAC samples and cell lines, miR-301a-3p was significantly up-regulated compared with matched non-tumor tissues and normal pancreatic ductal cells, respectively. Overexpression of miR-301a-3p enhanced PDAC cells colony, invasion and migration abilities in vitro as well as tumorigenicity in vivo. Furthermore, SMAD4 was identified as a target gene of miR-301a-3p by cell as well as mice xenograft experiments. In PDAC tissue microarray, a significantly inverse correlation between miR-301a-3p ISH scores and SMAD4 IHC scores were observed in both tumor and corresponding non-tumor tissues. CONCLUSION: MiR-301a-3p functions as a novel oncogene in PDAC and the oncogenic activity may involve its inhibition of the target gene SMAD4.